Multi-wavelength fiber laser generation by using optical wavelength conversion - Shirazi, M.R.; De La Rue, R.M.; Harun, Sulaiman Wadi; Ahmad, Harith (IOP Publishing, 2014)
A multi-wavelength fiber laser source is proposed and demonstrated by using simple, efficient wavelength conversion of a multi-wavelength Brillouin fiber laser (MBFL) assisted by four-wave mixing (FWM) processes. The MBFL is generated by emitting a Brillouin pump (BP) at the wavelength 1530 nm into a dispersion compensating fiber (DCF) of length 7.7 km in a ring cavity. By using the MBFL and a tunable laser source (TLS) as a FWM pump, both amplified through an erbium-doped amplifier and injected into a 100 m long highly nonlinear fiber (HNLF), two bundles of multi-wavelength fiber lasers are operated by degenerate FWM processes. When the TLS is set in the L band wavelength region, the two bundles of multi-wavelength fiber lasers are generated simultaneously in the S and U band wavelength regions.